PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH PROVINSI SULAWESI BARAT - Nurafiah, Nurafiah; Suwanti, Suwanti; Arsyad, Muhammad (LPPM Universitas Muhammadiyah Mamuju, 2024)
This study aims to determine the Influence of Competence and Physical Work Environment on Employee Performance at the Office of the Financial Management and Regional Revenue Agency of West Sulawesi Province. Quantitative methods with primary data using questionnaire data results. Respondents in this study were employees at the financial management and regional revenue agency of West Sulawesi province. The data analysis processing technique used was multiple linear regression analysis, with a sample size of 92 respondents. The formula used in this study used multiple linear regression, validity test, reliability test, multiple linear regression, t test, f test. The results of the study show that the Competency Variable has a partial effect on employee performance at the Office of the Financial Management and Regional Revenue Agency of West Sulawesi Province with a significant value of 0.016, which is smaller than 0.05. The physical work environment variable has a partial effect on employee performance at the Office of the Financial Management and Regional Revenue Agency of West Sulawesi Province with a significant value of 0.009, which is smaller than 0.05. The Competency Variable and the physical work environment have a simultaneous effect on employee performance at the Office of the Financial Management and Regional Revenue Agency of West Sulawesi Province with a significant value of 0.000, which is smaller than 0.05.